Solidarity and its decoloniality in global health ethics - Ademola Kazeem Fayemi; David Gerrard Kirchhoffer; Bridget Pratt (International Journal for Equity in Health)
Abstract Solidarity is one of the emerging values in global health ethics, and a few pieces of bioethics literature link it to decoloniality. However, conceptions of solidarity in global health ethics are influenced primarily by Western perspectives, thus suggesting the decolonial needs to include non-Western perspectives. This article explores a decolonial interpretation of solidarity to enrich our understanding of solidarity. It employs a palaver approach, typical of African (Yorùbá) relational culture, in developing a conception of solidarity grounded in a beehive metaphor. Through a decolonial methodological approach, this article posits that a beehive metaphor allegorically symbolises solidarity. In this decolonial interpretive account, solidarity embeds relational virtues and duties that foster harmony. Solidarity is a positively oriented affective disposition with people with whom one shares similar circumstances for harmonious well-being through concerted efforts. This article addresses five potential objections to this account of solidarity in global health ethics and consequently explores what an African account of solidarity means for global health research funding. This article concludes that the palaver decolonial approach from the Global South has implications for expanding conceptual perspectives on solidarity in global health ethics.